Answer:
![-512x^{30}](https://tex.z-dn.net/?f=-512x%5E%7B30%7D)
Step-by-step explanation:
![(-4x^5)^2 = 16x^{10}\\(-2x^4)^5 = -32x^{20}\\16x^{10} * -32x^{20} = -512x^{30}](https://tex.z-dn.net/?f=%28-4x%5E5%29%5E2%20%3D%2016x%5E%7B10%7D%5C%5C%28-2x%5E4%29%5E5%20%3D%20-32x%5E%7B20%7D%5C%5C16x%5E%7B10%7D%20%2A%20-32x%5E%7B20%7D%20%3D%20-512x%5E%7B30%7D)
What do you want me to solve for?
Answer:
B : y − 3 = 2/3 ⋅ ( x − 3 )
Step-by-step explanation:
Always, ALWAYS remeber this format: y = mx + b
In this equation, 'm' is the slope, and 'b' is the y-intercept
When you're trying to find a slope, remember that the equation is ![\frac{rise}{run}](https://tex.z-dn.net/?f=%5Cfrac%7Brise%7D%7Brun%7D)
When finding the rise and run, look at two points that are on the graph AND on the line as well. Essentially, make sure the points you're using are integers.
In this, case, the rise is -3, and the run is 2. This means that the slope is ![\frac{-3}{2}](https://tex.z-dn.net/?f=%5Cfrac%7B-3%7D%7B2%7D)
Now we have the first part of our equation:
y = -
+ b
But wait! How do we find b?
Sometimes you have to input x in order to find it, but only when you're not supplied with a graph. In this case, all you have to do is look!
The point of the line that is on the y-axis is called the y-intercept.
In this graph, the y-intercept is -1
Now we have our complete equation!
y = -
- 1
Good luck!
we are given a function
![f(x)=-6x](https://tex.z-dn.net/?f=f%28x%29%3D-6x)
First translation:
The graph of function is vertically stretched by a factor of 7
Whenever we vertically stretch any function by 'a' units
so, we can write it as
![g(x)=a\times f(x)](https://tex.z-dn.net/?f=g%28x%29%3Da%5Ctimes%20f%28x%29)
Here, it is vertically stretch by 7
so, we get
![g(x)=7\times -6x](https://tex.z-dn.net/?f=g%28x%29%3D7%5Ctimes%20-6x)
![g(x)=-42x](https://tex.z-dn.net/?f=g%28x%29%3D-42x)
Second translation:
Whenever we reflect any function about x-axis
we multiply y-value by -1
so, we can write it as
![g(x)=-f(x)](https://tex.z-dn.net/?f=g%28x%29%3D-f%28x%29)
Here , it is reflected in the x-axis
so, we can multiply by -1 to y-value
we get
![g(x)=-1\times -42x](https://tex.z-dn.net/?f=g%28x%29%3D-1%5Ctimes%20-42x)
.............Answer